2014
DOI: 10.1007/978-3-319-11662-4_19
|View full text |Cite
|
Sign up to set email alerts
|

Generalization Bounds for Time Series Prediction with Non-stationary Processes

Abstract: Abstract. This paper presents the first generalization bounds for time series prediction with a non-stationary mixing stochastic process. We prove Rademacher complexity learning bounds for both average-path generalization with non-stationary β-mixing processes and path-dependent generalization with non-stationary φ-mixing processes. Our guarantees are expressed in terms of β-or φ-mixing coefficients and a natural measure of discrepancy between training and target distributions. They admit as special cases prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Since the conditioning is on {n u = j}, the time slot difference between adjacent even/odd block is deterministic, and the β-mixing is not conditioned on the event. Similarly, it can be shown that E[1{A T (X o 1,t ) > }|n u = j] ≤α t,T,o (j) + m−1 j=1 β(a 2j ), (14) whereα t,T,h (j) Pr{A T (X h 1,t ) > |n u = j}, h ∈ {e, o}, and A T (X e 1,t ) (resp. A T (X o 1,t )) is obtained by replacing each block of data in X e 1,t (resp.…”
Section: Appendix a Proof Of Theoremmentioning
confidence: 95%
See 1 more Smart Citation
“…Since the conditioning is on {n u = j}, the time slot difference between adjacent even/odd block is deterministic, and the β-mixing is not conditioned on the event. Similarly, it can be shown that E[1{A T (X o 1,t ) > }|n u = j] ≤α t,T,o (j) + m−1 j=1 β(a 2j ), (14) whereα t,T,h (j) Pr{A T (X h 1,t ) > |n u = j}, h ∈ {e, o}, and A T (X e 1,t ) (resp. A T (X o 1,t )) is obtained by replacing each block of data in X e 1,t (resp.…”
Section: Appendix a Proof Of Theoremmentioning
confidence: 95%
“…For example, if ∆ T (t, T ) is small, then each term in (3) is small, and therefore results in a small average error. This approach is used in analyzing problems involving non-stationary stochastic processes [14].…”
Section: Problem Statementmentioning
confidence: 99%
“…For example, if ∆ T (t, T ) is small, then each term in (3) is small, which results in a small average offloading loss. This approach is central to the analyses of prediction problems involving nonstationary stochastic processes [33].…”
Section: Problem Statementmentioning
confidence: 99%
“…, K. In the above, (a) follows from the fact that the convex combination of the terms being greater than a constant implies that at least one of the term should be greater than the constant, and using the union bound. The inequality (b) is obtained by applying proposition 1 of [21] to the indicator function g 1{∆Ψ k,i,t > ǫ t,k } with expectation replaced by the conditional expectation E * | E c [αt:t] . Recall that the event E δ,τ corresponds to the error in decoding the correct index i * at time τ in Step 1 of the algorithm, and E [αt:t] = t τ =αt E δ,τ .…”
Section: Appendix C Proof Of Theoremmentioning
confidence: 99%